Music in the Service of Politics – Election Fight for Istanbul (2024) (Vade Nobiscum, tom XXIV/2024: Studia nad Bliskim Wschodem, 2024)
The purpose of this article is to provide a qualitative analysis of the content of the election songs of Istanbulʼs two major municipal candidates for the 2024 local elections. The text shows the differences in the narrative used by Turkeyʼs center-level ruling Justice and Development Party (AKP) and the center-level opposition and Istanbulʼs ruling Republican Peopleʼs Party (CHP). Then the way and main narrative emphases were related to the outcome of the March 31, 2024 local elections, showing their impact on the final outcome.